Influence of Al content on the mechanical properties and thermal stability in protective and oxidation atmospheres of Zr–Cr–Al–N coatings - Li, W. Z. (2013)
Tools have been used under very high temperature in recent decades. Therefore, coatings on tools are required to be thermally stable and excellent in oxidation-resistance. The introduction of Al into nitride coatings was considered as an effective way to improve the coating oxidation-resistance and thermal stability. Quaternary Zr–Cr–Al–N coatings were deposited with increasing Al contents by d.c. reactive magnetron sputtering. The coatings were annealed at 800 and 900 °C for 1 h in Ar + H2 atmosphere and exposed at 700 °C for 2 h and 1200 °C for 1 h in air, respectively. The hardness, Young's modulus, adhesive/cohesive strength and residual stress of as-deposited and annealed coatings were characterized by nanoindentation, scratch test and curvature measurement method. The results showed that the coating hardness and Young's modulus increased after post-annealing at 800 °C or 900 °C; the adhesive/cohesive strength decreased after annealing due to the substrate softening. The residual stress decreased after annealing and the lowest stress status depended on the crystallinity degree of the coating. XRD patterns showed mainly Cr2O3 formed in the Al-free, and a mixture of oxides of ZrO2 and Al2O3 in the high Al coatings after 1200 °C/1 h oxidation. N is still detected in the coatings, which indicates that the coatings are not fully oxidized being exposed to 700 °C for 2 h.